KASUS “DESAK MADE DARMAWATI” SEBAGAI REFLEKSI PEMBELAJARAN DALAM MENUMBUHKAN INSAN MODERAT DI INDONESIA - I Dewa Gede Darma Permana; Widya Ayu Candra; Fariz Alexander Lutfhianza (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Diversity has become a national identity that shows Indonesia's image as a country that respects differences. However, this has also become one of the triggers for conflict of disharmony in the form of cases of religious blasphemy. The “Desak Made Darmawati” case is an example of a religious blasphemy conflict in Indonesia. Through a viral video circulating on social media, he shows himself presenting statements that tend to corner Hindu religious beliefs. Reflecting on these problems, researchers are interested in studying more deeply the implications of the "Desak Made Darmawati" case as a reflection of learning in cultivating moderate people in Indonesia. In this research, several problem formulations were formulated, namely related to the chronology of cases, the urgency of religious moderation in Indonesia, as well as reflections on learning from the "Desak Made Darmawati" case. This research uses a qualitative type of research with a case study approach, followed by using data collection methods, namely library or literature studies, as well as Miles and Huberman's interactive data analysis techniques. The results of this research show that the implementation of religious moderation is still an urgent matter to prevent religious polemics. On this basis, the case of "Desak Made Darmawati" can provide a reflection of learning for religious people to become moderate people, especially from a humanist, religious and legal perspective in Indonesia.